An aggressive nonconsumptive effect mediates pest control and multipredator interactions in a coffee agroecosystem. Issue 7 (22nd June 2022) - Morris, Jonathan R.; Perfecto, Ivette
Abstract: Natural pest control is an alternative to pesticide use in agriculture, and may help to curb insect declines and promote crop production. Nonconsumptive interactions in natural pest control that historically have received far less attention than consumptive interactions, may have distinct impacts on pest damage suppression and may also mediate positive multipredator interactions. Additionally, when nonconsumptive effects are driven by natural enemy aggression, variation in alternative resources for enemies may impact the strength of pest control. Here we study control of the coffee berry borer (CBB), Hypothenemus hampei, by a keystone arboreal ant species, Azteca sericeasur, which exhibits a nonconsumptive effect on CBB by throwing them off coffee plants. We conducted two experiments to investigate: (1) if the strength of this behavior is driven by spatial or temporal variability in scale insect density (an alternative resource that Azteca tends for honeydew), (2) if this behavior mediates positive interactions between Azteca and other ground‐foraging ants, and (3) the effect this behavior has on the overall suppression of CBB damage in multipredator scenarios. Our behavioral experiment showed that nearly all interactions between Azteca and CBB are nonconsumptive and that this behavior occurs more frequently in the dry season and with higher densities of scale insects on coffee branches. Our multipredator experiment revealed that borers thrown off coffee plants by Azteca can survive and potentially damage other nearby plants but may be suppressed by ground‐foraging ants. Although we found no non‐additive effects between Azteca and ground‐foraging ants on overall CBB damage, together, both species resulted in the lowest level of plant damage with the subsequent reduction in "spillover" damage caused by thrown CBB, indicating spatial complementarity between predators. These results present a unique case of natural pest control, in which damage suppression is driven almost exclusively by nonconsumptive natural enemy aggression, as opposed to consumption or prey behavioral changes. Furthermore, our results demonstrate the variability that may occur in nonconsumptive pest control interactions when natural enemy aggressive behavior is impacted by alternative resources, and also show how these nonconsumptive effects can mediate positive interactions between natural enemies to enhance overall crop damage reduction.